Sustainable Practices in Organic Agriculture: Reducing Environmental Impact and Improving Efficiency (International Seven Journal of Multidisciplinary, 2023)
Organic agriculture provides an ecologically sound alternative to conventional farming by emphasizing biodiversity, soil health, and reduced chemical input. This article explores key sustainable practices that help minimize environmental impact and enhance efficiency in organic systems. Crop rotation improves soil fertility and disrupts pest cycles, particularly through the use of nitrogen-fixing legumes. Composting transforms organic waste into valuable humus, boosting soil structure, water retention, and microbial activity. Biological pest control replaces synthetic pesticides with natural predators, preserving ecosystem balance and protecting pollinators. Additional strategies such as agroforestry, efficient water management, and cover cropping further enhance system resilience, nutrient cycling, and erosion control. Collectively, these practices demonstrate that organic farming can maintain productivity while promoting environmental sustainability. As global demand for sustainable food systems increases, science-based organic methods offer a promising path toward resilient and regenerative agriculture.